Carbohydrates as organic raw materials III : developed from a workshop organized by the Carbohydrate Research Foundation Wageningen, the Netherlands November 28-29, 1994 - Bekkum, Herman van; Röper, Harald; Voragen, A. G. J. (VCH, 1996)
This volume is the continuation of a successful book series devoted to an increasingly vital subject: the utilization of carbohydrates as chemical raw materials. Sixteen contributions present an overview of current research thereby covering several new topics which were not dealt with in the preceding volumes:. - production and use of inulin. - lactose: its manufacture and physico-chemical properties. - lactic acid production and utilization. - bulking agents: polydextrose. - alkyl polyglucoside, a carbohydrate-based surfactant. As more than sixty percent of the authors come from industry, thi.